Rekonstruksi Epistimologi Ilmu Ushul Fikih Berbasis Ilmu Sejarah - Badruzaman, Badruzaman; Musofa, Ade (AL-ADYAN, 2018)
This research focuses on Hasan Hanafi's thought study of "Epistemological Reconstruction of the Science of Jurisprudence Based on Historical Sciences". From the results of the study found several findings; 1). Hasan Hanafi is a figure who is very concerned about efforts to revive the spirit and spirit (revitalization) of Ushul Fiqh Science by using a historical approach. According to him the dimensions of history and humanity are important factors in order to approach the conceptions and methodology of the Ummah of Fiqh. Actually the historical and human dimensions are found in the standard methodology of the Ummah Fiqh, but this historical dimension has long been "extinct" and detached from the Ushul Fiqh when the development process of Science took place and manifested itself in the process of developing this knowledge. So that in fact according to Hasan Hanafi, the historical dimension is essentially manifested in all elements of Usul Fiqh, namely in ill adillah syar’iyah, thuruq al istinbat and al ahkam al syar'iiyah. This historical dimension is represented by Hasan Hanafi with both keywords, namely "history" and "human"; 2). Hasan Hanafi is a person who cares about the existence of the Science of Ushul Fiqh, in order that he says the importance of efforts to revitalize the Ushul Fiqh methodology. Revitalization in Hasan Hanafi's thinking is an attempt to renew and adjust the methodology of the Ummah of Fiqh based on the conditions of social settings and the realities of humanity and the developing sciences, but this effort starts from tradition and the treasure of the Ushul Fiqh methodology built by earlier scholars. With such efforts, it is hoped that the renewal of the methodology of the Uthul Fiqh on the one hand can solve contemporary legal problems that are increasingly complicated, but on the other hand are not uprooted from the roots and genealogy of the Ushul Fiqh methodology; 3). The thought of the Ushul Fiqh Hasan Hanafi is very relevant to the efforts to reactualize Islamic law. This is because there is a deep "awkwardness" in the thought of Usul Fiqh so that in the actual reality the Science of Usul Fiqh has been frozen. The significance of the thought of Ushul Fiqh Hasan Hanafi lies in the effort to revive the vital spirit and spirit of this Science by using a historical approach. That is, that the human and historical dimensions are one thing that must be involved in the legal process; 4). The historical thinking of the Ustadh Fiqh Hasan Hanafi which is covered in the human dimension and history actually has roots in Hasan Hanafi's thoughts and projects about al Turas wa al Tajdid (Tradition and Renewal). Because of the loss of the human dimension and history in the tradition and the treasures of Muslim thought are the main problems which are the cause of the lack of progressivity in the traditions and actions of Muslims.